Fatty Acid Profile of Yellowfin Tuna Eye (Thunnus albacares) and Oil Sardine Muscle (Sardinella longiceps) - Renuka, V.; Anandan, R.; Suseela, M.; Ravishankar, C. N.; Sivaraman, G. K. (Fishery Technology, 2016)
In the present study, fatty acid profile of yellowfin tuna eye (YFTE) was investigated. Proximate analysis of YFTE revealed the presence of high fat content (12.0%) and moderate protein content (10.2%). A comparison was made between the fatty acid composition of YFTE and sardine oil. Higher poly unsaturated fatty acid content was found in YFTE (48.8%) compared to oil sardine (30.0%). Ratio of docosahexaenoic acid (DHA) content to the total fatty acids of YFTE was 36.72% which was higher compared to oil sardine (8.67%). However, EPA content of oil sardine was higher (16.8%) than YFTE (7.07%). DHA/EPA ratio and n-3/n-6 ratio of YFTE were 5.25 and 8.97 respectively. Palmitoleic acid was the principal mono unsaturated fatty acid (MUFA) present in YFTE and oil sardine. The present study revealed that yellow fin tuna eye could be a potential source of omega-3 fatty acids.